Radicals Everywhere

Algebra Level 4

If a , b , c a,b,c are real numbers such that
a 2 + b a 2 + c b 3 = 1 2 c 2 , \sqrt{a - 2} + \sqrt{b - a - 2} + \sqrt{c - b- 3} = \frac{1}{2}c - 2,
find 2 a + 3 b + 4 c \sqrt{2a + 3b + 4c} .


The answer is 8.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Karim Fawaz
Jun 14, 2016

Relevant wiki: Radical Equations - Intermediate

a 2 + b a 2 + c b 3 = 1 2 c 2 \sqrt{a - 2} + \sqrt{b - a - 2} + \sqrt{c - b- 3} = \frac{1}{2}c - 2

Multiplying by 2 we get:

2 a 2 + 2 b a 2 + 2 c b 3 = c 4 2\sqrt{a - 2} + 2\sqrt{b - a - 2} + 2\sqrt{c - b- 3} = c - 4

c 4 2 a 2 2 b a 2 2 c b 3 = 0 c - 4 - 2\sqrt{a - 2} - 2\sqrt{b - a - 2} - 2\sqrt{c - b- 3} = 0

( a 2 2 a 2 + 1 ) + ( b a 2 2 b a 2 + 1 ) + ( c b 3 2 c b 3 + 1 ) = 0 (a - 2 - 2\sqrt{a - 2} + 1) + (b - a - 2 - 2\sqrt{b - a - 2} + 1) + (c - b - 3 - 2\sqrt{c - b- 3} + 1) = 0

( a 2 1 ) 2 + ( b a 2 1 ) 2 + ( c b 3 1 ) 2 = 0 (\sqrt{a - 2} - 1) ^ {2} + (\sqrt{b - a - 2} - 1) ^ 2 + (\sqrt{c - b- 3} - 1) ^ 2 = 0

a - 2 = 1 ==> a = 3

b - a - 2 = 1 ==> b = 6

c - b - 3 = 1 ==> c = 10

2 b + 3 b + 4 c = 6 + 18 + 40 = 8 \sqrt{2b + 3b + 4c} = \sqrt{6 + 18 + 40} = 8

Answer = 8

Moderator note:

Note that you made the implicit assumption that a , b , c a,b,c are real numbers. I have since edited that into the question.

Did the same .nice question

Aditya Kumar - 4 years, 12 months ago

I also do this

VIneEt PaHurKar - 4 years, 12 months ago
Patrick Chatain
Jun 25, 2016

Relevant wiki: Applying the Arithmetic Mean Geometric Mean Inequality

It is clear that a 2 a-2 , b a 2 b-a-2 and c b 3 c-b-3 are non-negative,

Then applying AM-GM on ( a 2 ) (a-2) and 1 we have a 1 2 a 2 \frac{a-1}{2}\geq\sqrt{a-2}

Now apply AM-GM on ( b a 2 ) (b-a-2) and 1 to get b a 1 2 b a 2 \frac{b-a-1}{2}\geq\sqrt{b-a-2}

And finally AM-GM on ( c b 3 ) (c-b-3) and 1 to get c b 2 2 c b 3 \frac{c-b-2}{2}\geq\sqrt{c-b-3}

Adding all three we have a 2 + b a 2 + c b 3 1 2 c 2 \sqrt{a-2}+\sqrt{b-a-2}+\sqrt{c-b-3}\leq\frac{1}{2}c-2

The equation asks us for strict equality which for AM-GM only happens when all the terms are equal so,

a 2 = 1 a = 3 a-2=1 \implies a=3

b a 2 = 1 b = 6 b-a-2=1 \implies b=6

c b 3 = 1 c = 10 c-b-3=1 \implies c=10

Thus 2 a + 3 b + 4 c = 8 \sqrt{2a+3b+4c}=8

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...